Innovative performance of Brazilian public higher educational institutions: Analysis of the remuneration of research groups and companies - Thais Assis de Souza; Luiz Guilherme Rodrigues Antunes; Angélica da Silva Azevedo; Giulia Oliveira Angélico; Andre Luiz Zambalde (Innovation & Management Review, 2019)
Purpose - The purpose of this paper is to identify the compensation between research groups and companies that contribute the most for the innovative performance of Brazilian public higher educational institutions (PHEI), using as database the 2010's tabular plan from CNPq's Directory of Research Groups. Design/methodology/approach Descriptive and multivariate statistical techniques such as spearman correlation, cluster analysis, ANOVA and discriminant analysis were used. Findings Compensations that contribute the most for the updating of the PHEI are identified as transfer of financial resources from the partner to the group; providing grants for the group; transfer of material supplies to partner's activities; temporary physical transfer of human resources from the group to the activities conducted by the partner; other forms of compensation that do not fit in the previous categories; and partnering with transfers of resources of any kind going in any direction. Research limitations/implications As a limitation, it is pointed out the discontinuity of the tabular plan, which presents 2010 as the last available data. Practical implications The results can contribute to programs and policies to encourage innovation within universities. Originality/value It may be inferred that the stimulus to specific compensations may expand the quantitative idea of interaction points between the university and companies, linking qualitative aspects, which leads to an understanding that such interactions may, in fact, contribute directly to the activity of generating and spreading knowledge and innovation.
Keywords: 650; Process innovation; Public-private partnerships; Regional airports